Resiliensi Kognitif dan Motivasi Belajar Anak Broken Home: Studi pada Siswa Madrasah Ibtidaiyah Al-Ikhlas Ancaran - Wida Nengsih; Septi Gumiandari (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
The phenomenon of broken home families among elementary school students has become a significant social and psychological issue affecting learning motivation, emotional stability, character development, and academic achievement. This study aims to analyze the relationship between incomplete family conditions and students’ learning motivation, as well as the role of cognitive resilience, social support, and the school environment in maintaining academic achievement among students at MI Al Ikhlas Ancaran. Specifically, this study examines: (1) students’ cognitive conditions and learning motivation, (2) factors influencing cognitive resilience, (3) the role of Islamic Religious Education (PAI) in supporting learning motivation, and (4) Islamic value-based strategies to strengthen students’ cognitive resilience and learning motivation. This study employed a qualitative descriptive approach using observation, in-depth interviews, and documentation as data collection techniques. The participants included students from broken home families, Islamic Religious Education teachers, and homeroom teachers. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while validity was ensured through source and method triangulation. The findings indicate that students from broken home families generally possess relatively good cognitive resilience, enabling them to adapt to academic challenges and manage emotional stress effectively. Their learning motivation was categorized as moderate to good, reflecting strong internal encouragement to achieve despite family difficulties. The study also found that Islamic value-based strategies effectively strengthen cognitive resilience and learning motivation. Furthermore, a positive relationship exists between cognitive resilience and learning motivation, where higher resilience contributes to stronger learning motivation. Supportive family environments, madrasah settings, and positive peer relationships were identified as important factors in enhancing students’ resilience and academic motivation.